Radiologic findings of polypoid pyeloureteritis: a case report - Michael Phillipi, BA; Cassidy Tung, BA; Thomas Duong, MD; Ryan O'Connell, MD; Roozbeh Houshyar, MD (Radiology Case Reports)
Polypoid pyeloureteritis is a rare benign exophytic mucosal lesion of the renal pelvis and ureter caused by recurrent inflammation. Risk factors include a history of radiation therapy, colovesical fistulas, or calculi. To our knowledge, we present the first documented case of polypoid pyeloureteritis with radiologic, pathologic, and clinical correlation. A 74-year-old male with a history of right papillary renal cell carcinoma status-post nephrectomy and recurrent nephrolithiasis presented for computed tomography urography for carcinoma surveillance. Computed tomography urography revealed urothelial thickening at the left renal pelvis along with small polypoid filling defects in the left renal collecting system at the ureteropelvic junction, as well as a 3mm nonobstructing stone. Biopsy of the lesion confirmed the diagnosis of polypoid pyelitis with ureteritis. Lithotripsy for stone removal was administered at the time of biopsy, and fulguration of the mass was performed. At the time of 1-year follow-up the patient denied any complaints, including urinary symptoms. Imaging was once again remarkable for extensive urothelial thickening of the left renal pelvis and proximal ureter that demonstrated subtle nodularity, consistent with known polypoid pyeloureteritis. Clinical context and pathologic findings should be considered to differentiate benign polypoid lesions from urothelial neoplasms after observing urothelial thickening and filling defects on computed tomography urography. If the lesion is non-neoplastic, fulguration combined with removal of the irritant may serve as an alternative management for surgical excision.